2000
DOI: 10.1007/s002130000417
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor as a mediator of the effects of glutamate in the development of long-lasting sensitization to stimulant drugs: studies in the rat

Abstract: We argue that repeated exposure to stimulant drugs increases the demands on dopaminergic cell functioning, and, by stimulating glutamate release, recruits neurotrophic and neuroprotective substances such as bFGF. We propose that the actions of these factors, in turn, give rise to long-lasting neuronal adaptations that underlie sensitized responding to further drug exposure. Possible mechanisms whereby bFGF participates in the development of sensitization, including interactions with other neurotrophic factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 151 publications
1
35
0
4
Order By: Relevance
“…Exposure to AMPH enhances cocaine self-administration N Suto et al sensitization normally observed in the VTA such as D 2 DA autoreceptor subsensitivity (Wolf et al, 1994) and increased basic fibroblast growth factor, which through its effects on astrocytic function may affect the function of dopaminergic neurons (Flores and Stewart, 2000). The present results are consistent with these findings.…”
Section: Induction Of Sensitization By Amph Requires Activation Of Glsupporting
confidence: 90%
“…Exposure to AMPH enhances cocaine self-administration N Suto et al sensitization normally observed in the VTA such as D 2 DA autoreceptor subsensitivity (Wolf et al, 1994) and increased basic fibroblast growth factor, which through its effects on astrocytic function may affect the function of dopaminergic neurons (Flores and Stewart, 2000). The present results are consistent with these findings.…”
Section: Induction Of Sensitization By Amph Requires Activation Of Glsupporting
confidence: 90%
“…Following repeated cocaine injections or self-administration, increased numbers of dendritic spines and spine density are observed in reward-related brain regions such as the PFC Kolb, 1997, 1999;Robinson et al, 2001). Such structural changes could be regulated by neurotrophic factors, such as bFGF, as they promote neuron differentiation, neurogenesis, and experience-dependent plasticity (Aoyagi et al, 1994;Wagner et al, 1999;Flores and Stewart, 2000b). Following chronic or acute cocaine administration, bFGF mRNA expression is increased in reward-related brain regions such as the PFC (Fumagalli et al, 2006), and we showed that bFGF protein expression is similarly increased in IL-mPFC following cocaine self-administration.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulant drug use results in structural and functional changes in reward-related brain regions (Flores and Stewart, 2000b;Pickens et al, 2011). For example, expansion of dendritic arbors on dopaminergic neurons in the ventral tegmental area (VTA) occurs following stimulant drug administration (Mueller et al, 2006), and both dendritic length and spine density are increased in the prefrontal cortex (PFC) and nucleus accumbens following prolonged withdrawal Kolb, 1997, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules are differentially expressed in the bHR and bLR rat lines (19,29) and have been previously implicated in addiction-related behaviors (e.g., refs. [30][31][32]. We have shown that administration of FGF2 early in life increases the acquisition of cocaine self-administration in adulthood (33) and renders bLRs more bHR-like (34), supporting a role for FGF2 as a neuromolecular antecedent of drugtaking behavior (18,35).…”
mentioning
confidence: 81%